2022
DOI: 10.1111/bcp.15330
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis risk after beta‐blocker exposure: Description of a pharmacovigilance signal

Abstract: Aim We aimed to investigate French pharmacovigilance data. The objective was to characterize psoriatic conditions that occurred after beta‐blocker (BB) exposure and bring to light a possible pharmacovigilance signal. Methods Spontaneous reports of psoriatic conditions recorded in the French National Pharmacovigilance Database (FPVD) between 1985 and 2019 were extracted. We performed a retrospective, descriptive analysis of reports linked to BB exposure. Association between psoriasis risk and BB exposure was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In patients with psoriatic arthritis, BP should be lowered according to the general antihypertensive treatment recommendations, preferentially with RAS inhibitors and CCBs. BBs may trigger or worsen psoriasis and should be avoided if possible or carefully used in the presence of compelling indications [1545] (Table 16). Glucose control should be considered in patients with hypertension and psoriatic arthritis [1546].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…In patients with psoriatic arthritis, BP should be lowered according to the general antihypertensive treatment recommendations, preferentially with RAS inhibitors and CCBs. BBs may trigger or worsen psoriasis and should be avoided if possible or carefully used in the presence of compelling indications [1545] (Table 16). Glucose control should be considered in patients with hypertension and psoriatic arthritis [1546].…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…In the comparative analyses, we provided novel evidence that H2RAs exposure was associated with similar decreased all-cause mortality as β-blockers exposure did, which demonstrated that H2RAs had parallel anti-HF effect with β-blockers, especially for medium- and long-term outcomes, and strongly indicated that H2RAs might be, at least in part, an ideal kind of substitution to β-blockers in the treatment of HF because of their common pharmacological effects (i.e., down-regulation of cAMP and negative chronotropic and inotropic effects). It is noteworthy that, although β-blockers are one of the key recommended treatments for HF currently, the intrinsic disadvantages of this kind of drugs inevitably lead to relatively low drug adherence and even a series of adverse events in clinical practice ( Garcia et al, 2021 ; Azzouz et al, 2022 ). In this regard, H2RAs may have certain advantages over β-blockers.…”
Section: Discussionmentioning
confidence: 99%